Analisis Efektivitas Pembinaan Iman Anak Menggunakan Model CIPP (Context, Input, Process, Product) di Stasi Santo Yakobus Paroki Santo Padre Pio Helvetia - Angelina Sijabat; Petrus Simarmata (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
The present study aims to analyse the effectiveness of children's faith formation in Stasi Santo Yakobus Sukadono, Paroki Santo Padre Pio Helvetia, by using the CIPP (Context, Input, Process, Product) evaluation model. The present research employs a qualitative approach, utilising triangulation techniques in the form of observation, interviews, and documentation. The context component underscores the congruence between the program's objectives and the Church's vision, while also addressing the needs of the local community. The input aspect of the evaluation process encompasses the quality of the coaching staff, the availability of facilities and infrastructure, as well as the involvement of parents and dewan pastoral stasi. The process component focuses on the consistency of implementation and the methods used, including participatory approaches and liturgical activities. The product aspect of the programme has been found to engender an enhancement in spirituality, moral character, and active involvement of children in church life. The results indicate that the programme of faith formation has been effective, is pertinent to the contemporary context, and exerts a significant influence on the development of children's faith. Nevertheless, there is a necessity for the enhancement of coaching education, the more effective utilisation of digital media, and a deeperening of the collaboration between the Church and the family. It is anticipated that these findings will serve as a valuable contribution to the development of contextual and holistic faith education within the Catholic Church.